Making of village: the dynamics of adivasi rural life in India - Sen, Ashok kumar (Landon Routledge, 2021)
Tracing the historical journey of a village from inception to maturity is at once fascinating and epistemically rewarding. Experiences of this journey can be better appreciated in the light of the homologies and differences between historical and other genres of writings, broadly characterised as village studies. For the sake of convenience, this is elaborated in this chapter under three categories: writings by colonial ethnographers administrators, the sociological and anthropological writings produced immediately after Indian independence and later, and finally, the village ethnographic works by a wide spectrum of scholars.
Keywords: Indigenous people: India- social- conditions; Indigenous people: India ethnic identity; Indigenous people: India politics and government